¿Y Nosotros, Qué?: Moving beyond the Margins in a Community Change Initiative. - Quiñones, Sandra; Ares, Nancy; Padela, Maryam Razvi; Hopper, Mindy; Webster, Stephanie (Anthropology & Education Quarterly, 2011)
Our ethnography focuses on an urban community change organization within a predominantly African American and Latino population. Latino Critical Race Theory and Critical Race Theory help us understand the Spanish speakers' positioning and how particularities of Latinas/os' experience challenged power relations and group cohesion. Our findings illustrate tensions and contradictions of black-brown communities working in tandem to work against oppression. We argue that manifestations of intergroup conflict negatively influenced the success of this effort. Urban environments are increasingly demographically diverse and understanding how cross-group dynamics are interpreted by traditionally marginalized populations is essential to ensuring the educational, economic, and social success of students, [community change initiative, social context of schooling, Latino Critical Race Theory (LatCrit), Latinos, African Americans] Reprinted by permission of the publisher.